Heteroptera (Hemiptera) from the Chaco National Park (Argentina) - Melo, María Cecilia (2011)
An inventory of aquatic and terrestrial Heteroptera (excluding Aradidae, Coreidae and Pentatomoidea), comprising 101 species in 23 families, collected in the Chaco National Park (NE Argentina) is presented. . Fifty species are new records to the Argentinean Chaco province, and six species represent new records to Argentina: Cryphula affinis (Distant), Valtissius distinctus (Distant) (Rhyparochromidae), Stenopoda subinermis Stål, Diaditus pilosicornis Bergroth (Reduviidae), Buenoa uhleri Truxal (Notonectidae), and Paravelia splendoris (Drake & Harris) (Veliidae).